DIRECTIVE SPEECH ACTS REALIZATION OF INDONESIAN EFL TEACHER - Cucu Suhartini; Yulianti Wulansari (University of Kuningan, 2015)
Abstract: This research examines the types and functions of directive speech act performed by an Indonesian EFL teacher in one senior high school in Kuningan, Indonesia. This study uses qualitative method. The data of this research were taken from the video transcription which contains directives spoken by the EFL teacher and analyzed based on Kreidler’s (1998) theory. The findings show that there are three types of directives used by the teacher. They are commands, requests, and suggestions. The most frequent type of directives performed is commands with 233 occurrences (94.8%). It was also found that there are five functions seized by the directives, they are elicitation, instruction, advice, threat, and attention-getter. The most frequent function of directives used is elicitation with 108 occurrences (44%). From the findings, it is concluded that the using of commands shows teacher’s dominance. Yet, this type of directives is not easily understood by the students. Therefore, it is suggested that the teacher should use other types of directives more, such as requests and suggestions, to encourage students’ participation.Keywords: pragmatics, speech act, directive speech act.